Conservation and Management Effectiveness of Similipal Biosphere Reserve, Orissa, India - Mishra, B. K. (Indian Forester, 2010)
Similipal Biosphere Reserve of northern Orissa is one among the seven such reserves of India that form a part of the World Network of Biosphere Reserves The overall objective of the Biosphere Reserve programme was to deal with one of the most important questions of reconciling conservation of biodiversity, quest for economic and social development, and maintenance of associated cultural values. Simlipal has been regularly receiving financial assistance from the Ministry of Environment and Forests (MoEF, GoI) under centrally sponsored scheme. Using a host of participatory evaluation methods, conservation and management success of Biosphere Reserve scheme at Simlipal was evaluated. Major outputs as per the project objectives are improved protection, ecological restoration of degraded forests, sustainable utilization of natural resource, better employment opportunities for the local communities, increased conservation awareness, and improved research-management interface and PA-People relationship. The qualitative outputs have generated the overall atmosphere for stakeholder's participation, women empowerment and implementation of sustainable development initiatives in the villages of Simlipal Biosphere Reserve.